MODERN WAYS AND MEANS OF MINIMIZATION OF HYDROCARBONS EMISSIONS AT STORAGE OF GASOLINES - Бойченко, С.; Яворська, М. (Science-based technologies, 2012)
Found the basic directions and ways to minimize emissions hydrocarbon during storage of gasoline. Also defined correlation between the properties of gasoline for the evaporation.